ANALISIS STRATEGI BERSAING DAN KAPABILITAS DINAMIS DALAM MENCIPTAKAN KEUNGGULAN BERSAING PADA PERUSAHAAN JASA LOGISTIK EKSPEDISI BARANG DI MUARA BARU JAKARTA: STRATEGI BERSAING DAN KAPABILITAS DINAMIS - Manan, Abdul; Willey , Victor; Lucas, Thomas (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This research was conducted at several logistics companies located in Muara Baru, Jakarta. The aim of this research is to observe competitive strategies and dynamic capabilities in creating competitive advantages in Goods Expedition logistics service companies in Muara Baru Jakarta. This research uses a quantitative approach to collect data through interviews and documents. Then use deductive reasoning to analyze the data. Data collection methods were carried out through interviews, surveys and questionnaires. A descriptive approach was used to analyze the data collected. The results of the analysis show that the dynamic capabilities explained in the previous chapter can be concluded that there is an influence of Dynamic Capabilities on competitive advantage, there is an influence of manager's Skills & Competencies on competitive advantage, there is an influence of manager's Innovative Ideas on competitive advantage and there is an influence of Entrepreneurial thinking on Excellence competitive.